Feather Fin - Cosgrove, Stephen; James, Robin, 1953- (Vero Beach, Fla. : Rourke Enterprises, 1984)
Warned against leaving the deep sea where he is safe, a young eel nevertheless goes exploring and becomes stranded on the beach.
"A Serendipity book."
Keywords: Children's stories, American; Eels -- Fiction